New species of Selasia Laporte, 1838 (Elateridae: Agrypninae: Drilini) from Nepal and Pakistan - Kundrata, Robin (Zootaxa, 2017)
The neotenic click-beetle genus Selasia Laporte, 1838 is distributed mainly in the tropical Africa, and only a few species are known from the Palaearctic and Oriental regions. Herein, I describe and figure two new Palaearctic species: Selasia nigrobrunnea sp. nov. from the western Nepal, and Selasia sabatinellii sp. nov. from Pakistan. Both species are compared with their Palaearctic congeners, and an updated identification key to Selasia species from the Palaearctic region is provided.